Pelatihan Pembuatan Media Pembelajaran Interaktif Berbasis Kahoot Bagi Pendidik di SMAS Islam Ibadurrahman - A Mutahharah; Ninik Astuti; Nurbaitul Afyan; Nurjannah; Andi Baso Kaswar (Sakura Digital Nusantara, 2023)
This training activity is motivated by the challenges faced by our partners, namely that most educators primarily use traditional teaching methods, relying on chalkboards and occasionally incorporating PowerPoint slides. A significant number of educators employ lecture-style teaching during the learning process, resulting in a classroom environment that becomes monotonous and causes students to lose focus. Consequently, learners are unable to concentrate on the lessons being delivered in the classroom. Therefore, there is a pressing need for engaging learning media that meet the needs of students and enhance their learning determination. This training program is specifically designed for educators at SMAS Islam Ibadurrahman, as many educators there encounter difficulties in applying various media or applications in teaching, especially in the field of mathematics. The objective of this training is to enhance the educators' ability to utilize existing technology, particularly the Kahoot platform, as a means of teaching. The aim is to make educators more creative and capable of increasing students' interest in learning. The training activities was focus on the used and creation of Kahoot-based learning media. The outcome of this initiative was expected to increased the knowledge and skills of educators at SMAS Islam Ibadurrahman regarding the use of Kahoot as a teaching tool in the classroom.